Survey Postur Ideal Anak Usia Smp Dikaitkan Dengan Profil Kebugaran Jasmani Kelas VII Smp Negeri Se Kecamatan Suruh Kabupaten Semarang Tahun 2020 (Universitas Negeri Semarang, 2021)
The purpose of this study is to find out the ideal posture of children with physical fitness profiles of grade VII public junior high school students in semarang district in 2020. This research uses a descriptive quantitative approach. Sampling techniques in this study using propotionate random sampling. The subject of this research was a grade 7 student at SMP Negeri in Suruh sub-district. Data retrieval techniques using measurement and documentation. The data analysis technique used is bivariate correlation with sig<value 0.05. Based on research conducted on the ideal posture of children (Body Mass Index and Body Length Composition) is associated with physical fitness profiles it can be concluded that body mass index (BMI) there is a negative relationship with the physical fitness profile of students with a significance value of p = 0.00 (sig < 0.05) and coefficient value r = -0.388. While the Body Length Composition of the 8 aspects examined there are 2 aspects that correlate with the degree of weak correlation that is the length of limbs against the run of 40 and 50 meters with a signification value of p = 0.044 (p = <0.05) and a correlation coefficient value of r = 0.218, the length of the limbs against the run 600, 800, and 1000 meters meter with signification value p=0.049 (p=<0.05) and correlation coefficient value r=0.213, thigh length torun 600, 800, and 1000 meters with a signification value of p=0.013 and correlation coefficient value r=0.268.